SINTESIS POLIANILIN YANG DIPERKAYA γ-Fe2O3 DARI PASIR BESI LOKAL SULAWESI TENGGARA UNTUK APLIKASI - Anton, Ardin; Nalis, M.; Taswito, C. C. N.; Agusu, La (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
This research is aimed to develop the radar absorbing material based on polyaniline enriched by γ-Fe2O3 synthetized from the sandstone. γ-Fe2O3 is, then, derived from calcination process of Fe3O4 powder at the temperature of 400-600oC. Fe3O4 powder itself is extracted from the local sandstone of South East Sulawesi area by using the co-precitipation method with both HCl and NH4OH act as the solvent and precitipation agent, respectively. The polyaniline is synthetized from its monomer, aniline, where both HCl and NH4OH are also used as a dopant and an oxydator agent, respectively. Effect of reaction pH on the crystal size of Fe3O4 is also investigated. The XRD spectrum shows that a rather high purity of Fe3O4 in nano size is being achieved at the pH value of 8 and 9. However, at a rather low pH value (6.5 and 7.5), the additional weak peaks in XRD spectrum shows the existence other metal compounds impurity. The crystal sizes is approximately 8.01 and 11.07 nm for pH value of 8 and 9. The VSM measurement result shows that the saturated magnetization value of Fe3O4 is 24.45 emu/g. The Fe3O4 is calcined at temperature of 500oC for 3 hours to get γ-Fe2O3. Finally, the polyaniline-γ-Fe2O3 composites were synthetized using an insitu polymerization method where the weight contents of γ-Fe2O3 are 5, 10, 15, and 20 percent. Those materials will be useful as a prospective application in radar absorbing materials technology at frequency ranges of 9-17 GHz. Keywords: polyaniline, γ-Fe2O3, co-precitipation, sandstone, radar absorbing materials